The Role of Psychological Adaptation in the Process of Self-Realization of Gifted Students - Sadova, Myroslava; Lapshun, Galyna; Samokhvalova, Iryna; Oglu Abdullayev, Vusal Elshad; Komarivska, Nadiia (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: The gifted students' ability for psychological adaptation determines their effectiveness in achieving self-realization and successfully addressing educational and professional challenges. Objective: The aim of the study was to assess the level of students' psychological adaptation and identify key factors affecting their academic and professional self-realization. The effectiveness of psychological interventions intended to improve adaptation processes was also analyzed. Methods: The study employed the following methods as the psychodiagnostic tools: Psychological Adaptation Scale, Rosenberg Self-Esteem Scale, Emotional Quotient Inventory, and Student Self-Efficacy Scale. Experimental interventions included psychological training. Correlation analysis, multiple regression, and t-tests for dependent samples were used for data analysis. Results: The results showed that the level of students' psychological adaptation increased from 3.85 to 4.45 (t = 5.20, p < 0.001) after psychological training. The level of stress resistance increased from 3.70 to 4.30 (t = 4.85, p < 0.001). The level of self-realization also increased from 3.95 to 4.55 (t = 4.95, p < 0.001). Correlation analysis revealed a significant positive relationship between students' emotional regulation, social support, and self-realization (r = 0.57, p < 0.01). Conclusion: The practical significance of the study is that psychological training effectively develops adaptive skills. This increases the level of students' self-realization, which can be used for the development of university support programs. The prospects for further research include expanding the sample and examining the long-term effects of the interventions.